Rituals of triumph in the Mediterranean world - Spalinger, Anthony John.; Armstrong, Jeremy. (Culture and History of the Ancient Near East, 2013)
Societies, both ancient and modern, have frequently celebrated and proclaimed their military victories through overt public demonstrations. In the ancient world, however, the most famous examples of this come from a single culture and period - Rome in the final years of the Roman Republic and early Roman Empire - while those from other cultures - such as Egypt, Greece, Neo-Assyria, and indeed other periods of Roman history - are generally unexplored. The aim of this volume is to present a more complete study of this phenomenon and offer a series of cultural reactions to successful military actions by various peoples of the ancient Mediterranean world, illustrating points of similarity and diversity, and demonstrating the complex and multifaceted nature of this trans-cultural practice. \'The book nevertheless represents a valuable collection of papers on a not so widely researched topic and is clearly a stepping stone for further research as indeed the editors intended it to be.\' Uros Matic, Universitaet Muenster